Impact of the soluble interleukin-2 receptor level in the relapsed or refractory phase on the clinical outcome of patients with diffuse large B-cell lymphoma. Issue 8 (3rd July 2019) - Umino, Kento; Fujiwara, Shin-Ichiro; Ikeda, Takashi; Kawaguchi, Shin-Ichiro; Toda, Yumiko; Ito, Shoko; Ochi, Shin-Ichi; Nagayama, Takashi; Mashima, Kiyomi; Minakata, Daisuke; Nakano, Hirofumi; Yamasaki, Ryoko; et al.
Abstract: This study sought to investigate the impact of the soluble interleukin-2 receptor level in the relapsed or refractory phase (r/r sIL-2R) on the clinical outcome in patients with diffuse large B-cell lymphoma (DLBCL). We determined the optimal cutoff value of r/r sIL-2R for disease progression within 6 months from salvage chemotherapy to be 861 U/mL. The high r/r sIL-2R group exhibited a significantly lower survival rate than the low r/r sIL-2R group (1-year event-free survival [EFS], 22.6% vs. 55.7%, p  < .001 and 1-year overall survival [OS], 45.9% vs. 75.1%, p  < .001). Independent significant correlations were observed between r/r sIL-2R and both inferior 1-year EFS and OS in a multivariate analysis (hazard ratio [HR]: 2.69, 95% CI: 1.61–4.51, p  < .001 and HR: 2.99, 95% CI: 1.57–5.70, p  < .001). This study demonstrates that r/r sIL-2R could be useful for predicting a poor prognosis in patients with r/r DLBCL.